2019
DOI: 10.1111/desc.12823
|View full text |Cite
|
Sign up to set email alerts
|

Development of approximate number sense across the elementary school years: A cross‐cultural longitudinal study

Abstract: In recent years, there has been growing interest among researchers in exploring approximate number sense (ANS)—the ability to estimate and discriminate quantities without the use of symbols. Despite the growing number of studies on ANS, there have been no cross‐cultural longitudinal studies to estimate both the development of ANS and the cross‐cultural differences in ANS growth trajectories. In this study, we aimed to estimate the developmental trajectories of ANS from the beginning of formal education to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 47 publications
0
35
1
Order By: Relevance
“…Our sample consisted of pupils from Russia and Kyrgyzstan. An estimation of cross-country differences in growth of ANS revealed that the rate growth was significantly lower in the Kyrgyz sample [24]. These differences might be partly explained by certain characteristics of educational processes in elementary school in the Kyrgyz sample Particularly, the class size was larger in the school in Kyrgyzstan than in Russia.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our sample consisted of pupils from Russia and Kyrgyzstan. An estimation of cross-country differences in growth of ANS revealed that the rate growth was significantly lower in the Kyrgyz sample [24]. These differences might be partly explained by certain characteristics of educational processes in elementary school in the Kyrgyz sample Particularly, the class size was larger in the school in Kyrgyzstan than in Russia.…”
Section: Discussionmentioning
confidence: 91%
“…21]. Growing precision of the ANS manifested as a decrease in Weber fraction (w) [21][22][23] or an increasing proportion of correct answers in nonsymbolic comparison tasks [24,25]. The peak of precision in ANS and smallest w occur near 30 years of age [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that academic achievement is largely related to the individual characteristics of basic cognitive processes, i.e., information processing speed, visuospatial working memory, and number sense [ 2 , 5 , 6 , 7 , 8 ], as well as higher-order cognitive processes, such as primarily fluid intelligence [ 1 , 3 , 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, basic cognitive traits, along with intelligence, explain up to 60% of the dispersion of academic success [ 5 ]. Additionally, studies report that the indicators of cognitive abilities are age-related and have unique developmental trajectories across schooling [ 6 , 27 , 28 ]. Thus, the trajectory of the development of information processing speed in childhood and adolescence is best described by quadratic dependency, showing an increase in the information processing speed indicators between the ages of 5 and 18, with periods of sharp increases and periods of relative stability [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%